1991
DOI: 10.1080/02724936.1991.11747518
|View full text |Cite
|
Sign up to set email alerts
|

The impact of medical services on trachoma in a Gambian village: antibiotics alone are not the answer

Abstract: We have measured the prevalence of active trachoma in children aged less than 15 years in the Gambian village of Keneba, which has had excellent free medical care and a continuous supply of antibiotics since 1974. The prevalence was 13%, with the peak prevalence (20%) occurring in the 2 to 3-year age group. Of 71 cases diagnosed, only 23 (33%) had complained of ocular symptoms in the previous 3 months, in spite of the fact that 66 (94%) had attended the clinic. Only five had been diagnosed as having trachoma b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…None of the participants, however, appreciated the link between childhood infection and the scarring sequelae of adulthood; this lack of association may impede compliance with mass antibiotic administrations, delay treatment-seeking behavior and hinder uptake of disease control behaviors. 14 , 23 Future public health education might focus on raising awareness of eye disease in children, the concept of asymptomatic disease and explaining the natural history of trachoma to nurture understanding.…”
Section: Discussionmentioning
confidence: 99%
“…None of the participants, however, appreciated the link between childhood infection and the scarring sequelae of adulthood; this lack of association may impede compliance with mass antibiotic administrations, delay treatment-seeking behavior and hinder uptake of disease control behaviors. 14 , 23 Future public health education might focus on raising awareness of eye disease in children, the concept of asymptomatic disease and explaining the natural history of trachoma to nurture understanding.…”
Section: Discussionmentioning
confidence: 99%
“…It was even reported that many of such mothers had cause to visit the local Health Centre (where the ointment was readily available) for some other health-related appointments in the course of this treatment, and yet failed to ask for the ointment in order that they might complete the treatment. 19 The lack of motivation to continue with the treatment may have stemmed from a lack of mental connection between this childhood eye infection and blindness from trichiasis later in life. Before any intervention efforts could be successful, there is a need to establish this link in people's minds, and active inflammatory trachoma, innocuous as it may appear, must be identified as a problem by the community dwellers themselves.…”
Section: Community Concepts Of Role and Their Implications For Trachomamentioning
confidence: 99%
“…Many active infections are asymptomatic and appear to cause little or no discomfort ( Mabey et al . 1991 ).…”
Section: Trachoma As a Diseasementioning
confidence: 99%
“…The need for provision of surgery and antibiotics is not in doubt, but on their own they are unlikely to be successful. When used rationally, antibiotics have a positive effect, but it is unrealistic to think that this can be maintained ( Mabey et al . 1991 ).…”
Section: The Transmission Of Trachomamentioning
confidence: 99%